Peran Komunikasi Internal Dalam Pencapaian Visi dan Penanaman Nilai Perusahaan Crediton Group Indonesia - Fransiska Oki Riang Setyana; Akhmad Edhy Aruman (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
This study aims to determine the role of internal communication in achieving the vision and value infusion of CreditOn Group Indonesia. The successful achievement of CreditOn's Company in Kazakhstan is a reference for CreditOn Group Indonesia in achieving its vision and work culture, but expectations and reality do not run smoothly in its implementation. This study uses the theory of organizational communication and internal communication or also known as employee communication theory. The researcher wants to know how CreditOn Indonesia delivers the vision and values ​from Top Management to employees in order to achieve the output that is expected to be achieved. This research uses a qualitative method with a constructivism paradigm because there is a reality that the company wants to build to achieve its vision and application of its values. The results of the study show that there are inefficiencies in using communication channels, noise in delivering the messages, timing of the delivery of messages in the term of communicating the vision and company’s values.